Influence of different agroecological conditions of southern Russia on quality indicators of raw milk - I. F. Gorlov; M. I. Slozhenkina; O. Y. Mishina; E. В. Karpenko; N. I. Mosolova (Юг России: экология, развитие)
Aim. To demonstrate the high adaptive abilities of dairy cattle to various ecosystems and natural zones of the Lower Volga at different times of the year. For the study we selected farms located in the steppe and semi-desert natural zones of the Volgograd region where animals of different breeds are reared.Material and Methods. Analysis was undertaken of the main indicators of raw milk quality, amino acid composition and environmental safety. Animals of all farms studied showed fairly high indicators of milk productivity in the climatic conditions of the Volgograd region, according to the standards of the breeds investigated.Results. The content of essential amino acids in cow milk for all groups varied depending on the breed and period of the year, generally reaching maximum values in winter. The calculation of amino acid scores showed that lysine is a limiting amino acid in animals of the Holstein-Friesian breed in the summer and autumn periods of lactation. The determination of chemical elements in milk during the summer period of lactation showed that all indicators are within acceptable concentrations, including heavy metals (lead, arsenic, cadmium, mercury).Conclusion. The research conducted confirms compliance of raw milk with standards in all farms studied for the main controlled indicators of quality and amino acid composition, content of chemical elements and allows recommendation of the milk produced for the production of all types of dairy and fermented milk products.